PENGARUH METODE PROBLEM SOLVING TERHADAP HASIL BELAJAR IPS DI SD - Rezkiani, Nofi; Rosnita, Sugiyono; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to analysis the effect of problem solving method in students? social science learning achievement on year-4 of Elementary School 56 Pontianak Barat. The method this research is experiment with the research form of quasi experimental design, with nonequivalent control gruop design. The population of this research was all of Year-4 students of Elementary School 56 Pontianak Barat. The sampel of this research specified with technique purposive sampling consist of 32 students in class IVA as control class and 30 students in class IVC as experiment class. The researcher collected the data by the measurement technique in using paper test have multiple choice form numbering 50 question. Based on count obtained an average of achievement post-test control class 59,69 and the average of achievement post-test experimental class 68,50 thus obtained tcount post-test data of 3.440 with ttable for ? =5% and df = 60 that mean 2,000, there were tcount > ttable so Ha was accepted. The effect size was categorized as medium effect since the ES value was 0,61. In conclusions, the effect of problem solving method is significant and effective for students? social science learning achievement on year-4 of Elementary School 56 Pontianak Barat. Key words: The effect, problem solving, achievement, social science.